Creating a new management university : tracking the strategy of Singapore Management University (SMU) in Singapore (1997-2019/20) /: tracking the strategy of Singapore Management University (SMU) in Singapore (1997-2019/20). (2022) - Thomas, Howard, 1943-; Wilson, Alex; Lee, Michelle P
No abstract available